Supply chain segmentation in the sporting goods industry - Roscoe, S.; Baker, P. (Taylor & Francis, 2014)
The purpose of this paper is to explore the factors that influence supply chain segmentation when selling to consumers through retail chains. The initial research is based on a review of supply chain segmentation literature and the application of relevant parameters to a specific case study, comprising two major brands in the sporting goods industry. The empirical research itself comprises semi-structured interviews, covering demand planning, sales, marketing and supply chain managers, supported by quantitative demand data. The case study demonstrates that a number of the existing frameworks are relevant but that none are adequate by themselves. It also shows the importance of linking segmentation of the end consumers to that of the retail intermediaries. The paper provides an exploratory supply chain segmentation framework for companies selling to end consumers through intermediary retailers, aligning their marketing, sales, demand planning and supply chain functions.